Hemorrhagic Fever in Adults at Kamphaengphet Hospital 2007 - Khontong, Rojjana (Journal of Health Science of Thailand, 2018)
A retrospective review was conducted by collecting data of DF and DHF patientsี hospital records at Kamphaengphet hospital from January 1 to December 31 2007. Descriptive statistics were used to describe and compare data between 54 DF and 179 DHF patients, totaling 233. Male to female ratio was 1.21:1. DHF patients were classified as 99 DHF grade 1 (55.3%), 55 in grade 2 (30.7%) and 25 DHF grade 3(14%). Seventeen patients with severe complications or unusual manifestation were referred to a more advance hospital. Most of them came to the hospital on day 3 or 4. The most common symptoms found in DF patients were high fever,tension headache,cough,nausea and vomiting while in DHF patients were high fever,tension headache,nausea,vomiting,poor appetite and myalgia. Tourniquet test was positive in 20 percent and 45.5 percent of DF and DHF patients respectively. The distinct change of complete blood count was that the white blood count decreased towards the end of febrile phase,especially 1-2 days before the decrease of body temperature. Platelet counts dropped to the range of 100,000-150,000 cell/mm3. The complications in DHF were abnormal bleeding, hypotension, shock, hypokalemia and sinus bradycardia. There was no hemoconcentration found in thalassemia patients but there was anemia and a need of pack red cell. Pregnant patients should be aware of dengue infection and early treatment.